THE PREVALENCE OF CHILD STUNTING BEFORE AND DURING THE COVID19 PANDEMIC ERA IN GENDING DISTRICT - Jose Giovanny; Nirwana Mila Safitri; Salvador Benedictus Borromeu; Sagung Putri Maharani; Nindya Amalia Biharjo Putri; Christian Jaya Sumarto Putra; Yudistira ..; Theresia Arum Hanitani; Bella Agustina Andreani; Julio Cesar Adhyaksa de Fatima; Yosephine Valentine Surya; Shallen Angelia Wijaya; Lukas Slamet Rihadi; Inge Wattimena; Florentina Sustini; Steven Wijono; Dewa Ayu Liona Dewi; Yudhiakuari Sincihu; Anisah Machmudah; Miza Nisrinah; Dwi Puspitasari (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: In Indonesia, the first COVID-19 cases were announced on March 2, 2020. The first two cases were found in Jakarta, and the number continues to grow over time. Stunting is a condition in which children experience growth disorders so that the child's height does not match their age. The COVID-19 pandemic increases the risk of acute nutritional problems (undernutrition and malnutrition) in vulnerable groups. Even chronic nutrition problems (Stunting) can increase if the COVID-19 lockdown is set for long. However, data from the SSGI in 2019, 2020, and 2021 show a decline in the prevalence of Stunting from year to year. Purpose: This study was conducted to determine a difference in child Stunting prevalence before and during the COVID-19 pandemic in the Gending District. Methods: This research is an observational analytic study with a cross-sectional study. The population in this study was a child with an age range of 2-5 years before and during the COVID-19 pandemic at the Gending Public Health Center. Results: From 317 total samples, 50 stunted children were found in the period before the pandemic and 25 stunted children during a pandemic. The prevalence of child Stunting before and during the COVID-19 pandemic decreased by 28% to 16.1%. Based on the Pearson Chi-Square Test analysis test, the prevalence of Stunting was significantly (p= 0.031) different before and during the COVID-19 pandemic. Conclusion: There are differences in child Stunting prevalence before and during the COVID-19 pandemic. Keywords: Pandemic, COVID-19, Stunting.